Protective Effects of Propolis and Probiotic Lactobacillus acidophilus against Carbon Tetrachloride-Induced Hepatotoxicity in Rats - Abdelkader Oumeddour; Djahida Zaroure; Raziqua Haroune; Rima Zaimeche; Karima Riane; Mohamed Sifour; Abdelkrim Tahraoui (Tabriz University of Medical Sciences, 2019)
Background: Propolis (PRS) and probiotic bacteria Lactobacillus are natural products used as dietary supplement for their therapeutic benefits. This study was performed to examine the possible hepatoprotective effect of PRS and probiotics (PRCs) against carbon tetrachloride-induced liver injury. Methods: Experimentally, intoxicated rats received 0.5 ml/kg CCl4 (i.p.) daily for six days, pretreated rats received per os PRS 100 mg/kg or PRCs 109 CFU for six days followed by a single dose of 0.5 ml/kg CCl4. Control groups received either PRS, PRCs or olive oil for six days. Then, serum biochemistry (total protein, cholesterol, triglycerides and albumin) and oxidative stress parameters were measured. Results: We showed that CCl4 treatment was associated with an increase of the serum aspartate amino transferase (AST), alanine aminotransferase (ALT), cholesterol and triglycerides levels. In parallel, serum total protein, albumin and blood sugar levels were significantly decreased. Regarding the oxidative stress parameters, catalase and glutathione S-transferase (GST) levels were lower, conversely to the lipid peroxidation (MDA). Conclusion: Our results strongly support that administration of PRS and PRCs may significantly protect liver against CCl4-induced toxicity by enhancing antioxidative stress pathway and preventing lipid peroxidation.